The Competence and Compellability of Witnesses - De Vos, Wouter (2016)
The competence and compellability of a witness should not be confused with the possible privileges which he might claim. Cowen & Carter 1 explain as follows: 'A competent witness is a person whom the law allows a party to ask. but not to compel, to evidence. A compellable witness is a person whom the law allows a party to compel to evidence. There are certain questions which a witness may refuse to answer if he so wishes. He is said to be privilege in respect of those questions. It should be clear, therefore, that competence without compellability (or bare competence) is not the same as privilege. Compellability is concerned with whether a witness can be forced by a party to evidence al all. Privilege is concerned with whether a witness who is already in the box is obliged to answer a particular question. The protection of privilege is exactly the same whether the witness is barely competent and of his own free will elected to give evidence or the witness is compellable and was forced to give evidence." It follows that a competent and compellable witness who wishes to rely on, for example, the privilege against self-incrimination may not refuse to enter the witness-box: he may only claim his privilege once the relevant question is put to him.